Quantitative chemical analysis - Harris, Daniel C.; Lucy, Charles A. (New York : WH Freeman, 2016)
Quantitative Chemical Analysis gives you a sound physical understanding of the principles of analytical chemistry and their applications in a variety of disciplines. The gold standard in analytical chemistry, Dan Harris$1 (BQuantitative Chemical Analysis provides a sound physical understanding of the principles of analytical chemistry and their applications in the disciplines.s
The Analytical Process -- 1 Chemical Measurements -- 2 Tools of the Trade -- 3 Experimental Error -- 4 Statistics -- 5 Quality Assurance and Calibration Methods -- 6 Chemical Equilibrium -- 7 Let the Titrations Begin -- 8 Activity and the Systematic Treatment of Equilibrium -- 9 Monoprotic Acid-Base Equilibria -- 10 Polyprotic Acid-Base Equilibria -- 11 Acid-Base Titrations -- 13 Advanced Topics in Equilibrium -- 14 Fundamentals of Electrochemistry -- 15 Electrodes and Potentiometry -- 17 Electroanalytical Techniques -- 18 Fundamentals of Spectrophotometry -- 19 Applications of Spectrophotometry -- 20 Spectrophotometers -- 21 Atomic Spectroscopy -- 22 Mass Spectroscopy -- 23 Introduction to Analytical Separations -- 27 Gravimetric and Combustion Analysis -- 28 Sample Preparation
Includes index.
Keywords: CHEMISTRY